Effect of telephone counselling on the rate and continuity of exclusive breastfeeding among mothers with late preterm infants: A randomized controlled trial - Azam Maleki; Marzieh Mohammadian; Gholamreza Badfar (حیات, 2022)
Background & Aim: Due to the importance of breastfeeding in the health of premature infants, the present study was conducted with the aim of determining the effect of telephone counseling on the continuity and breastfeeding status of mothers with late preterm infants. Methods & Materials: In this randomized controlled trial, 65 eligible mothers from Ahvaz in 2019-2020 were selected using the convenience sampling method and divided into two intervention and control groups using block randomization (with block sizes of 4). The routine care was provided for the control group. The intervention group received a daily telephone support counseling for 14 days after discharge. Data were collected using a questionnaire on the continuity of breastfeeding and breastfeeding status at the pre-counseling phase and then monthly up to four months after discharge. Data were analyzed using chi-square test, independent t-tests and Kaplan Meyer survival analysis at a significance level of 0.05 through the SPSS software version 16. Results: According to Kaplan Meyer survival analysis, the rate of exclusive breastfeeding interruption in the control group was higher than that of in the intervention group (5 vs. 8) but it was not statistically significant. Improvement of breastfeeding status one month after discharge was significantly different between the two groups (P=0.048). Conclusion: The results showed that telephone support counseling was effective in improving breastfeeding status up to the first month after discharge. Continuous telephone support counseling can be a good approach to improving breastfeeding and its continuity in the first month after discharge. Clinical trial registry: IRCT20150731023423N13